2019
DOI: 10.1002/acm2.12711
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of diagnostic reference levels in cardiac computed tomography

Abstract: The aim of this study was to determine diagnostic reference levels (DRLs) for cardiac computed tomography (CCT) in Jordan. Volume computed tomography dose index (CTDI vol ) and dose-length product (DLP) were collected from 228 CCTs performed at seven Jordanian hospitals specialized in cardiac CT. DRLs for cardiac CT were defined at the 75th percentile of CTDI vol and DLP. CTDI vol and DLP were collected from 30 successive cardiac CT in each center except for one center (18 scans). The 75th percentile of the CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Regarding the range of doses recorded, large variations were evident across the surveyed hospitals in reported CTDI vol and DLP values. This is in line with previous work, which has shown that variations may occur depending on CT scanner design (43,45) and the protocol employed (4547). The particular make and model of the CT scanner may lead to some variation in doses owing to inherent differences such as filtration, beam geometry, number of detector rows, scattered X-rays, and noise value calculations (48,49).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the range of doses recorded, large variations were evident across the surveyed hospitals in reported CTDI vol and DLP values. This is in line with previous work, which has shown that variations may occur depending on CT scanner design (43,45) and the protocol employed (4547). The particular make and model of the CT scanner may lead to some variation in doses owing to inherent differences such as filtration, beam geometry, number of detector rows, scattered X-rays, and noise value calculations (48,49).…”
Section: Discussionsupporting
confidence: 92%
“…Routine quality control is conducted for scanners in Jordan (43). Automated tube current modulation and iterative reconstruction were used in all systems except hospitals 6 and 12.…”
Section: Methodsmentioning
confidence: 99%
“…Emerging evidence demonstrates a patient’s absorbed dose depends on the computed tomography (CT) scanner radiation dose output during CT examinations ( 1 - 3 ). The most common scanner output dose metrics for CT systems are the volumetric CT dose index (CTDI vol ) and dose-length product (DLP) ( 4 , 5 ). CTDI vol and DLP indicate the absorbed dose of polymethyl methacrylate (PMMA) phantoms with defined diameters of 16 and 32 cm for the head and body, respectively ( 6 - 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…While this may be a new noninvasive method for detecting functional coronary stenosis, it risks increasing radiation exposure. Therefore, we aim to verify and compare the dose of radiation exposure for 320‐row dynamic CCTA with that for standard CCTA and the latest CCTA diagnostic reference levels (DRLs) for Japan and Western countries 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we aim to verify and compare the dose of radiation exposure for 320-row dynamic CCTA with that for standard CCTA and the latest CCTA diagnostic reference levels (DRLs) for Japan and Western countries. 16,17 2 | METHODS…”
Section: Introductionmentioning
confidence: 99%